Cicakman: A study on glocalization in Malaysian superhero movie genre / Foo Mei Lee - Foo , Mei Lee (2017)
The numbers of superhero films growing since we have approached the new millennium. A superhero film is a film that is focused on the actions of one or more individuals who usually possess superhuman abilities and are dedicated to protecting the public from super villain or rival with bad intentions. These films usually feature action, fantasy or science fiction elements, which also include the origin of their special powers. The superhero film have performed relatively well in the box office. This prompts a new phenomenon, producing sequel. Dietz, J. (2011) found that sequels also performed well in box office. Malaysia renowned filmmaker in KRU Studio also jumps on to the bandwagon by producing Malaysia first superhero movie Cicakman (Feature Film, n.d.). The Cicakman film made history, breaking the opening-day record by grossing RM350, 000 on its first day of release (ï¿½8 Malaysian-Made Films,ï¿½n.d.). This film had 2 more sequels following to the huge success. The success has prompted mixed responses from both positive and negative reviewers. Some of the movie reviewers have indicated that Cicakman have a lot of global influences and almost identical to Westerners superhero movie. However, there is a new Hollywood genre called global-local film following a new model in the global filmmaking industry known as glocalisation. Glocalisation is not just a model for filmmaking industry; it is also known as a marketing tool for other trade. It is a combination of global and local trend to enhance the end product. A study on Cicakman movie has been conducted to assess the Cicakman filmmaking process and identify the elements of glocalisation in it.